cFOS expression in the prefrontal cortex correlates with altered cerebral metabolism in developing germ-free mice - Pate, Trinity; Anthony, Daniel C.; Radford-Smith, Daniel E. (Frontiers in Molecular Neuroscience, 2023)
Introduction The microbiota plays a critical role in modulating various aspects of host physiology, particularly through the microbiota-gut-brain (MGB) axis. However, the mechanisms that transduce and affect gut-to-brain communication are still not well understood. Recent studies have demonstrated that dysbiosis of the microbiome is associated with anxiety and depressive symptoms, which are common complications of metabolic syndrome. Germ-free (GF) animal models offer a valuable tool for studying the causal effects of microbiota on the host. Methods We employed gene expression and nuclear magnetic resonance (NMR)-based metabolomic techniques to investigate the relationships between brain plasticity and immune gene expression, peripheral immunity, and cerebral and liver metabolism in GF and specific pathogen-free (SPF) mice. Results Our principal findings revealed that brain acetate (p = 0.012) was significantly reduced in GF relative to SPF mice, whereas glutamate (p = 0.0013), glutamine (p = 0.0006), and N-acetyl aspartate (p = 0.0046) metabolites were increased. Notably, cFOS mRNA expression, which was significantly decreased in the prefrontal cortex of GF mice relative to SPF mice (p = 0.044), correlated with the abundance of a number of key brain metabolites altered by the GF phenotype, including glutamate and glutamine. Discussion These results highlight the connection between the GF phenotype, altered brain metabolism, and immediate-early gene expression. The study provides insight into potential mechanisms by which microbiota can regulate neurotransmission through modulation of the host’s brain and liver metabolome, which may have implications for stress-related psychiatric disorders such as anxiety.